Furture job trend in design - Abd Rahman, Khairul Aidil Azlin (International Journal of Innovative Science, Engineering & Technology, 2020)
The global agenda is shifting from a knowledge economy to the humanization economy age. Creativity, and design areas have interconnected with each other in term of development of a product to be realized. Design knowledge is more towards understanding the human experience which involved the conversion of tacit knowledge to explicit knowledge. As a comparison, design thinking and design process creates values in designing products; meanwhile knowledge conversion process creates values in knowledge. IR 4.0 is expected to bring about a major shift in society. In this regard the need for high skill design workforce is increasing because of the acceleration of emerging technologies. Many jobs will be diminishing and new design jobs that will grow in the coming future. Most sought after by employers will include problem solving, creative thinking, emotional intelligence and interpersonal skills. Such skills can be directly gained through leadership education.